THE INFLUENCE OF PRODUCT QUALITY AND PRICE ON THE DECISION TO VISIT AT RUMAH SERABI 74 LARANGAN, TANGERANG CITY, BANTEN PROVINCE - Reno Catelya Dira Oktavia; Linda Desafitri RB (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
The research objective was to determine the effect of product quality and price on the decision to visit Surabi 74 Restaurant. This type of research was quantitative descriptive with multiple regression analysis. The sample is 100 respondents with accidental sampling technique. The results of the study show that product quality has a significant effect on visiting decisions. Product quality has a significant influence on the decision to visit Surabi 74 Restaurant, because serving food with good taste, soft texture, and fresh ingredients, customers will tend to be satisfied and more likely to return. Price also has an important influence on customers' visiting decisions to Rumah Makan Surabi 74, because the price of food and drinks at Rumah Makan Surabi 74 is affordable in proportion to the quality, customers will feel that they are getting good value for the money they spend